A study for the prediction of corona power on electrostatic precipitator based on simple and easy two-dimensional electrostatic simulation - Cho, Chang-Hee; Kim, Dong-Hoon; Park, Sang-Eon (International Journal of Engineering and Technology, 2020)
This study examines how the designing of an electrostatic precipitator can be carried out in a simple way. While it is of value to find out the theoretical values of design parameters using three-dimensional finite element model and numerical method, this study shows that employ-ing a two-dimensional finite element model and easily usable public-domain program is equally simple and fast. Variations of some physical properties occurring between an electrode and a duct are expressed using two design parameters. In this process, the design of the experi-ment and the response surface method are used based on the two-dimensional finite element model, as well as electrostatic simulation. A test using an electrostatic precipitator is performed and it is confirmed that a variation of corona power by the test is most similar with the varia-tion of stored energy by the simulation. A conversion factor that can predict corona power with the response surface function for the stored energy is proposed.Â Â